Avaliação da eficácia da vacina viral convencional contra a circovirose suína em leitões sob condições de campo no Brasil - Raquel Lopes Hungueri dos Santos (2010)
The effects of implementing a fully viral and conventional vaccine against porcine circovirus type 2 in pigs at weaning were studied. A total of 1140 piglets, males and females, were divided into two groups: vaccinated (single dose of 0.5 ml of vaccine) and control (not vaccinated). All animals were evaluated from the application of the experimental treatment until market. The application of the vaccine had no significant adverse effects. Vaccinated males compared to males in the control group had a higher slaughter weight of 2.73 kg (p = 0.029) and a higher average daily gain of 0.025 Kg (p = 0.027). In contrast, females had no difference in body weight or average daily gain between control and vaccination groups. However, there was a greater final body weight of 1.50 kg (p = 0.07) in females vaccinated compared to the control group. There was no significant difference between groups regarding mortality and culling rates, coughing, sneezing and diarrhea, medication use, pneumonia index, pathological and histopathological lesions, and antibody titration. These data indicate that vaccination against PCV-2 is safe and effective in improving the final weight and the average daily gain in piglets vaccinated under field conditions in Brazil.